O-111 ACP, a fundamental cultural novelty: Lections from the maps-trial. (1st September 2015) - Krones, Tanja; Loupatatzis, BS; Otto, T; Karzig, I
Abstract : Background: Advance Care Planning (ACP) and the use of evidence based decision aids for a shared decision making process (SDM), thoroughly informing patients in order to decide on future health care are two important strategies to support patients in making reasonable heath care choices. Both are until now rarely implemented in Switzerland and ACP and SDM including Decision aids in the ACP process is also quite rare internationally. Aim: To develop and test an ACP intervention including Decision aid videos and decision aids in the facilitation process, adapted to a university hospital population in the Swiss context under the auspices of the swiss national science foundation (NFP67 end of life) Methods: Randomised double blind (patient and responsible physician) controlled trial (MAPS trial: Multiprofessional Advance Care Planning and shared decision making for end of life care) the effect of an ACP/SDM intervention (up to three ACP sessions with trained facilitators, also integrating decision aid videos and decision aids, control group discharge talk with the social service) in a university hospital population of patients with a positive surprise question (physician would not be surprised if the patient died within the next 12 months. The main endpoints are wishes on end of life care (resuscitation, intubation, artificial feeding, dialysis, last place of care) known by primary caregivers and physician or wishes respected (if applicable) 6 months after the intervention. Results: After designing and implementing the intervention (decision aids, advance directive, facilitator training), recruitment started end of July 2013 and finished in December 2014. The last patient for the 6 months follow up, when the main end points are measured will take place in July 2015. Results will be available at the ACPEL conference All in all 1349 patients and their surrogates were screened for eligibility, 115 (planned: 180) could be included and radomised into intervention or control arm. Discussion and conclusion: From what we can say so far is that although ACP is very much appreciated by most patients and their caregivers included in the trial and by many professionals involved, to newly implement such a programme in a university hospital setting for the population of very sick patients in the last months of their life is an enormous effort and encounters several obstacles, even if final results may show the desired effects. For our hospital ACP was such a fundamental cultural novelty that many academic detailings and sessions were necessary to build the ground for making ACP possible in a trustful atmosphere. We also faced unforeseen resistances not by patients but by many surrogates to be involved in that process of talking about patients wishes also in cases when the heath situation might deteriorate, leading to many screening failures. We will discuss these experiences in the light of our first results.